Integrative Model for Strengthening Religious Character Based on Religious Activities at MTs Miftahul Ulum - Zainab, Siti; Prasetya, Benny; Khoiriyah, Khoiriyah; Syahrin, Muhammad Alfi (Green Publisher, 2026)
Over the past decade, religious character education has re-emerged as an academic response to the moral and spiritual crisis among younger generations amid globalization and the secularization of values. Although numerous studies have examined religious character education, research that specifically constructs an integrative model based on religious activities institutionalized within madrasah culture remains relatively limited. This study aims to analyze religious activities, identify an integrative model for strengthening religious character, and examine the implications of this model at MTs Miftahul Ulum, Probolinggo Regency. This research employs a qualitative approach with a phenomenological method. Data were collected through participatory observation, in-depth interviews with the head of the madrasah, Islamic Religious Education teachers, and students, as well as documentation, and were analyzed using the interactive model proposed by Miles and Huberman. The findings indicate that religious activities such as Qur’anic recitation, congregational prayers, tahfiz programs, the 3S program (greeting, smiling, and courteous interaction), and socio-religious activities function as the core of the madrasah’s institutional culture. This study identifies an integrative model encompassing three principal domains: an integrative model of a religious curriculum within instructional processes, an integrative model of habituation and the internalization of worship practices, and an integrative model of a religious school culture. The implementation of this model strengthens students’ religious character, particularly in terms of discipline, courtesy, responsibility, learning focus, and social awareness. The study contributes theoretically by offering a contextual integrative model and provides practical implications for the long-term development of religious character education in madrasahs.